Odpowiedź :
w(x)=x3+ax2-bx-b
w(1) = 0 i w(2) = 0
{1 + a - b - b = 0
{8 + 4a - 2b - b = 0
{a - 2b = -1 /*(-4)
{4a - 3b = -8
{-4a + 8b = 4
{4a - 3b = -8
5b = -4
b = -4/5 ==> a = 2b - 1 = -13/5
a = -13/5
b = -4/5
w(1) = 0 i w(2) = 0
{1 + a - b - b = 0
{8 + 4a - 2b - b = 0
{a - 2b = -1 /*(-4)
{4a - 3b = -8
{-4a + 8b = 4
{4a - 3b = -8
5b = -4
b = -4/5 ==> a = 2b - 1 = -13/5
a = -13/5
b = -4/5
w(x)=x3+ax2-bx-b pierwiastki :1 i 2
w(1)= 1+a-b-b=0
w(2)=8+4a-2b-b=0
{1+a-2b=0 czyli a =2b-1
{8+4a-3b=0
8+4(2b-1)-3b=0
8+8b-4-3b=0
5b=-4
b=-4/5
a = 2*(-4/5)-1
a= -8/5-1=-13/5
zatem
w(x) = x³-13/5x²+4/5+4/5
w(1)= 1+a-b-b=0
w(2)=8+4a-2b-b=0
{1+a-2b=0 czyli a =2b-1
{8+4a-3b=0
8+4(2b-1)-3b=0
8+8b-4-3b=0
5b=-4
b=-4/5
a = 2*(-4/5)-1
a= -8/5-1=-13/5
zatem
w(x) = x³-13/5x²+4/5+4/5